Mater semper certa est, pater semper incertus est: vida escolar de adolescentes - Andre Soares da Cunha (2013)
This research intended to investigate possible consequences in the school life of teenagers, from their family configurations way. The issue was approached by the Psychoanalysis bias and has as its starting point the evolution of the concept of Father, especially in the works of Freud and Lacan. In addition, there was the necessity of understanding part of the historical path of the changes in family configurations, as well as some of the issues involving the problems presented in the school environment. The research proposal has origins in the malaise in education scenery seen from the researcher experience as a History teacher in public and private education systems. Among different situations, one stands out in that environment, which refers to the usual speech that relates directly experienced problems in the educational environment to some students family configuration, due to the fact that they differentiate from the ones said traditional (father, mother and offspring). In this sense, a question arose: did those students from family configurations which are different from the model biological father, mother and child, for this reason, contribute to the increase in problems at school? The choice of subjects was made through the indications from leaders of two public schools and a private one in the city of Piumhi (one was public and the other was private) and Capitólio (public), both in the State of Minas Gerais. Furthermore, a documentary analysis of the students was made. The intersection of information from both data sources allowed the choice of 14 subjects who composed this research. The semi-structured interviews with the teenagers were another instrument used as data collection. To support some of the hypotheses that emerged after the data analysis, it was necessary a theoretical study about the concept of femininity in the psychoanalytic theory of Lacanian orientation, aiming the attempt to understand the relationship of adolescents and their mothers, that seems to influence their successful school lives. Besides, it was found that, in a general way, mothers have strong influence in their children school life, while the fathers are partially or totally absent. At most, it was realized that the problems experienced in the school environment relate more to the inadequacy of the school system than to the type of family configuration of which students are part of.